PENERAPAN METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN PADA SISWA KELAS VIII C SMP WIDYA SAKTI DENPASAR TAHUN PELAJARAN 2023/2024 - Ari, Luh Putu Gita Sahalia; Susrawan, I Nyoman Adi; Erawan, Dewa Gede Bambang (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research is classroom action research (PTK) which aims to (1) find out that the CIRC method can improve the ability to write short stories in class VIII C students at Widya Sakti Denpasar Middle School in the 2023/2024 academic year, (2) find out the right steps in application of the CIRC method to improve short story writing skills. Data collection used observation methods and test methods. The data obtained was analyzed using qualitative analysis and quantitative analysis methods. The research results obtained showed that there had been an increase in the test scores as follows: (1) In cycle I the average score of the initial test (pretest) increased from 3.69 to 5.69. (2) Cycle II increased the average value from 5.69 to 8.19. The steps for implementing the CIRC method are as follows: 1) the teacher asks students what they know about short stories, 2) the teacher asks students to group together by counting. Each group consists of 4-5 students. 3) the teacher explains the meaning of short stories, the purpose of writing short stories, the steps for writing short stories and examples of short stories, 4) the teacher distributes short story texts to each group and asks them to read the short story texts with their friends, 5) the teacher invites students to analyze the use of spelling according to EYD, the diction used, the harmony and suitability of the content of the story with the themes presented in the short story text that has been distributed 6) after the teacher explains, students are invited to ask questions 7) The teacher gives assignments to students in each group to create a story short with a theme given by the teacher. 8) after the students create a short story the teacher assigns each group to present the results of the short story they have created 9) the teacher provides feedback to each group. ABSTRAK Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan (1) mengetahui bahwa dengan metode CIRC dapat meningkatkan kemampuan menulis cerita pendek pada siswa kelas VIII C SMP Widya Sakti Denpasar Tahun Pelajaran 2023/2024, (2) mengetahui langkah-langkah yang tepat dalam penerapan metode CIRC untuk meningkatkan kemampuan menulis cerita pendek. Pengumpulan data yang digunakan dengan metode observasi dan metode tes. Data yang diperoleh dianalisis dengan metode analisis kualitatif dan analisis kuantitatif. Hasil penelitian yang menunjukkan terjadi peningkatan yaitu dari nilai tes sebagai berikut: (1) Pada siklus I nilai rata-rata tes awal (pretest) meningkat dari 3,69 menjadi 5,69. (2) Siklus II peningkatan nilai rata-rata dari 5,69 menjadi 8,19. langkah-langkah penerapan metode CIRC sebagai berikut: 1) guru memberi pertanyaan kepada siswa apa yang mereka ketahui tentang cerita pendek, 2) guru meminta siswa untuk berkelompok dengan cara berhitung. Setiap kelompok terdiri atas 4-5 siswa. 3) guru menjelaskan pengertian cerita pendek, tujuan menulis cerita pendek, langkah-langkah menulis cerita pendek dan contoh cerita pendek, 4) guru membagikan teks cerita pendek kepada setiap kelompok dan meminta untuk membaca teks cerita pendek bersama teman-temannya, 5) guru mengajak siswa untuk menganalisis penggunaan ejaan sesuai EYD, diksi yang digunakan, keselarasan dan kesesuaian isi cerita dengan tema yang disajikan dalam teks cerita pendek yang sudah dibagikan 6) setelah guru menjelaskan maka siswa dipersilahkan untuk bertanya 7) Guru memberikan tugas disetiap kelompok untuk membuat cerita pendek dengan tema yang diberikan guru. 8) setelah siswa membuat cerita pendek guru menugaskan masing-masing kelompok untuk mempresentasikannya 9) guru memberikan tanggapan kepada masing-masing kelompok.